Trends of scientific production on health assessment in Brazil - Tatiana Maria Melo Guimarães dos Santos; Naldiana Cerqueira Silva; Lídya Tolstenko Nogueira; Lílian Machado Vilarinho; Geandra Batista Lima Nunes (Rev Rene)
This is a bibliographic review study with the objective of describing the trends of scientifi c production on health evaluation in Brazil between 2000 and 2009. The SCIELO (Scientifi c Electronic Library Online) database was used, with the descriptor: health evaluation, yielding 47 articles. It was found out that 48.9% of the publications dealt with programs and projects developed in Primary Health Care, with emphasis on the Family Health Strategy, highlighting accessibility, effectiveness, user satisfaction and the monitoring of actions. It was concluded that the trends and innovations in the health evaluation fi eld are mainly focused on primary care, which is undergoing restructuring with the introduction of new strategies, one of which is evaluation as a daily practice, which facilitates decision making and management.